2016
DOI: 10.1111/wvn.12162
|View full text |Cite
|
Sign up to set email alerts
|

Portable Video Media Versus Standard Verbal Communication in Surgical Information Delivery to Nurses: A Prospective Multicenter, Randomized Controlled Crossover Trial

Abstract: PVM provides a novel method for providing education to nurses that improves knowledge retention and satisfaction with the educational process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…The construction and validation of an educational video for deaf people about CPR is relevant because it provides a didactic resource that can be used for training of a great number of people with standardized instructions and also corroborates with a self-directed and flexible learning process, because it provides the possibility of autonomy for the learners to watch the video in any moment they prefer and as many times as they deem it necessary 8 - 10 . Such educational technology can also contribute to the practice of health and education professionals who work with deaf students, to enable accessibility and empowerment to act correctly in cases of CA.…”
Section: Introductionmentioning
confidence: 96%
“…The construction and validation of an educational video for deaf people about CPR is relevant because it provides a didactic resource that can be used for training of a great number of people with standardized instructions and also corroborates with a self-directed and flexible learning process, because it provides the possibility of autonomy for the learners to watch the video in any moment they prefer and as many times as they deem it necessary 8 - 10 . Such educational technology can also contribute to the practice of health and education professionals who work with deaf students, to enable accessibility and empowerment to act correctly in cases of CA.…”
Section: Introductionmentioning
confidence: 96%
“…Also, the pains, anxiety and fears during the examination may induce excess motility, causing a possible impairment of image quality and prolonged examination. It is believed that video is more capable of sending information and improving the receivers' understanding of messages [11].…”
Section: Discussionmentioning
confidence: 99%
“…Patients are usually provided with training to know procedure details by literal, verbal and graphic manners [8]. Researchers have indicated that video is more comprehensive and acceptable [11][12] for examinees to understand the theory and operation details of a certain approach. Moreover, emerging attention is paid to radiation generated in DSA.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of YouTube on a wide range of devices, such as personal portable media devices e.g. smart phones, makes accessing video media remarkably simple [19,20]. This resulted in a high uptake of video media as the main educational tool in our present study for both the initial education of the Seldinger technique and as a multimedia learning tool, allowing 70% of the difficult catheterisations in our present study to be done without the direct supervision of a urology registrar or urologist for this urological emergency.…”
Section: Discussionmentioning
confidence: 99%